1999
DOI: 10.1053/jvet.1999.0154
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oral Isoxsuprine and Pentoxifylline on Digital and Laminar Blood Flow in Healthy Horses

Abstract: Neither isoxsuprine nor pentoxifylline increased blood flow to the digit or dorsal laminae in healthy horses. Acepromazine caused an increased blood flow to the digit. Based on the results of this study acetylpromazine potentially would have a greater effect on improving digital blood flow than oral isoxsuprine or pentoxifylline when treating ischemic conditions of the foot in horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 17 publications
2
41
0
1
Order By: Relevance
“…Regarding the improvement of laminar tissue circulation blood, which in the chronical phase happens to be compromised and often show larger areas of necrosis, INGLE-FEHR & BAXTER (1999) had observed that acepromazine increases digital blood flow, differently from the observation after pentoxifylline and isoxsuprine administration.…”
Section: Treatmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding the improvement of laminar tissue circulation blood, which in the chronical phase happens to be compromised and often show larger areas of necrosis, INGLE-FEHR & BAXTER (1999) had observed that acepromazine increases digital blood flow, differently from the observation after pentoxifylline and isoxsuprine administration.…”
Section: Treatmentmentioning
confidence: 97%
“…The acepromazine may also be used to restrict movement of the horse by mild sedation, and there is a vasodilator effect (INGLE-FEHR & BAXTER, 1999), despite of the controversial use this stage.…”
Section: Treatmentmentioning
confidence: 99%
“…Moreover, the averaging over 120 sec as the time of the sampling interval {∆T (s)} for the data of static blood flow has already been proposed [11], and the frequency information over Fs/2=1/(2∆T)=0.0042 Hz have ever been excluded as the critical frequency by Nyquist under the sampling theorem [16]. Based on this, the minimum resolution component of 1/256=0.0039 Hz, defined by the recording time in 256 sec, was decided in this study.…”
Section: Frequency Analysismentioning
confidence: 99%
“…Isoxuprine (Ingle-Fehr and Baxter 1999) and topical nitroglycerine (Gilhooly et al 2005) have been shown to have no effect on digital perfusion. Although acepromazine effectively increases total blood flow to the digit, there is little evidence to support this as being beneficial in the prevention or treatment of sepsis-related laminitis (Leise et al 2007).…”
Section: Laminitis Prophylaxismentioning
confidence: 99%
“…Traditionally researchers hypothesised laminitis was a form of ischaemia reperfusion injury (Robinson 1990;Trout et al 1990;Hood et al 1993;Molyneux et al 1994;Eaton et al 1995;Hinckley et al 1995;Bailey and Elliott 1998;Ingle-Fehr and Baxter 1998;Ingle-Fehr and Baxter 1999;Schneider et al 1999;Rosenstein et al 2000;Bailey et al 2002;Elliott et al 2003;Berhane et al 2006). However, the variation in techniques for measuring lamellar perfusion (Hood, Amoss et al 1978;Allen, Clark et al 1990;Trout, Hornof et al 1990;Eaton, Allen et al 1995;Hinckley, Fearn et al 1995;Adair, Goble et al 2000;Hood, Wagner et al 2001) along with the use of different experimental models for laminitis induction yielded conflicting results.…”
Section: Theories On Laminitis Pathogenesismentioning
confidence: 99%